The Influence of Psychological, Spiritual Dimensions and Modernization of the Tax Administration System on Individual Taxpayer Compliance - Rika Selpi Yonita; Halimatusyadiah Halimatusyadiah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of moral obligations, spirituality and modernization of the tax administration system on individual taxpayer compliance. The data used in this study are primary data. Primary data was obtained from questionnaires distributed to Individual Taxpayers in Bengkulu City. The number of questionnaires distributed was 100 questionnaires. The data were analyzed using multiple linear regression analysis using the SPSS program. The results showed that spirituality has a positive and significant influence on individual taxpayer compliance while moral obligations and modernization of the tax administration system do not significantly affect individual taxpayer compliance.